Integrated metasurfaces for re-envisioning a near-future disruptive optical platform - Younghwan Yang; Junhwa Seong; Minseok Choi; Junkyeong Park; Gyeongtae Kim; Hongyoon Kim; Junhyeon Jeong; Chunghwan Jung; Joohoon Kim; Gyoseon Jeon; Kyung-il Lee; Dong Hyun Yoon; et al. (Light: Science & Applications, 2023)
Abstract Metasurfaces have been continuously garnering attention in both scientific and industrial fields, owing to their unprecedented wavefront manipulation capabilities using arranged subwavelength artificial structures. To date, research has mainly focused on the full control of electromagnetic characteristics, including polarization, phase, amplitude, and even frequencies. Consequently, versatile possibilities of electromagnetic wave control have been achieved, yielding practical optical components such as metalenses, beam-steerers, metaholograms, and sensors. Current research is now focused on integrating the aforementioned metasurfaces with other standard optical components (e.g., light-emitting diodes, charged-coupled devices, micro-electro-mechanical systems, liquid crystals, heaters, refractive optical elements, planar waveguides, optical fibers, etc.) for commercialization with miniaturization trends of optical devices. Herein, this review describes and classifies metasurface-integrated optical components, and subsequently discusses their promising applications with metasurface-integrated optical platforms including those of augmented/virtual reality, light detection and ranging, and sensors. In conclusion, this review presents several challenges and prospects that are prevalent in the field in order to accelerate the commercialization of metasurfaces-integrated optical platforms.